RANCANG BANGUN WEBSITE PADA SMP NEGERI 3 KOTA PAGAR ALAM - Puspita, Desi; Oktisa, Rina (Universitas Bina Darma, 2016)
Abstracts: The purpose of this study is the Build website at SMP Negeri 3 Kota Pagar Alam in order to help users get information about the activities of student learning, teaching, school achievement, teachers and students. With her website at SMP Negeri 3 Kota Pagar Alam is expected to provide fast, precise and accurate for those in need. Currently in SMP Negeri 3 Kota Pagar Alam despite the availability of the Internet however, the unavailability of a website to facilitate the search of information about SMP Negeri 3 Kota Pagar Alam. Systems Development Method used method of Web Engineering with stage-phases: Custumer Communication, Planning, Modeling, Contruction and Deployment. Design using UML and Programming using PHP. The results of the research the availability of Website SMP Negeri 3 Kota Pagar Alam can be accessed by the user wanted to know information SMP Negeri 3 Kota Pagar Alam. Keywords: Website, Design, Web Engineering, UML and PHP